Preparation method of ZnO nanoparticles

By controlling reaction conditions with poly-C DNA templates, ZnO nanoparticles with uniform spindle-shaped structures are synthesized, addressing dispersibility issues and enhancing antibacterial efficacy for medical dressings.

CN119191336APending Publication Date: 2024-12-27CENT SOUTH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311162.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing methods for synthesizing zinc oxide nanomaterials using DNA templates result in nanoparticles with poor dispersibility and irregular structures, making them unsuitable for medical dressings.

Method used

A method involving the use of poly-C DNA with specific base lengths and concentrations to control the reaction conditions, resulting in ZnO nanoparticles with a uniform spindle-shaped structure and improved dispersibility, suitable for medical applications.

Benefits of technology

The method produces ZnO nanoparticles with a particle size less than 300 nm and high uniformity, demonstrating effective antibacterial properties against Staphylococcus aureus and Escherichia coli, and showing promise in wound antibacterial treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191336A_ABST
    Figure CN119191336A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of ZnO nano-particles, which comprises the following steps: uniformly mixing Zn salt in a poly-C DNA aqueous solution with the concentration of 2-8 [mu] M, adjusting the pH value to be alkaline, and incubating at room temperature to obtain the ZnO nano-particles with fusiform structures. The particle size of the ZnO nano-particles obtained by the preparation method is less than 300nm, the ZnO nano-particles have good antibacterial activity, and the ZnO nano-particles can be prepared into an external preparation to be used for wound surface antibiosis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano materials, and in particular to a method for preparing ZnO nano particles. Background Art

[0002] Antibacterial dressings with metal as the main component have become a commonly used auxiliary treatment method in the clinical treatment of chronic infected wounds. Compared with silver and copper, zinc, as an essential trace element in the human body, has a higher safe dose, and zinc oxide (ZnO) is also recognized by the FDA as a "generally recognized as safe" (GRAS). The antibacterial activity of zinc oxide mainly depends on its direct contact with bacteria. Therefore, nanomaterials made of zinc oxide can be used as a good antibacterial raw material for the treatment of wound infections.

[0003] The synthesis of zinc oxide nanomaterials usually includes high-temperature calcination, mechanical grinding, etc. In comparison, the process of synthesizing zinc oxide nanomaterials using biomacromolecules as templates is simple and the conditions are mild. In addition, the functional modification of zinc oxide nanomaterials can be achieved by introducing biomaterials at the interface. The literature Liu Yufei. Synthesis of zinc oxide nanochain structure using DNA as template [D]. Tianjin: Tianjin University, 2007. discloses a method of using DNA template to adsorb zinc ions and react in situ to generate zinc oxide nanoparticles. First, fish sperm DNA and zinc nitrate are mixed in an aqueous solution to allow them to be fully adsorbed, and then a diethanolamine aqueous solution is added under a water bath to form zinc oxide nanoparticles with chain structures on the DNA template. However, the zinc oxide nanomaterials synthesized by this method rely on the DNA chain structure and are difficult to achieve good dispersibility in medical dressings. Summary of the invention

[0004] The purpose of the present invention is to improve the existing technology and obtain a new type of ZnO nanoparticles. The particle size of the ZnO nanoparticles is less than 300nm, and they present a uniform spindle-shaped structure. DNA is fixed in the structure and the ZnO nanoparticles can be used as an antibacterial component of medical dressings.

[0005] A method for preparing ZnO nanoparticles, characterized by comprising the following steps: placing Zn salt in a poly-C DNA aqueous solution with a concentration of 2-8 μM and mixing, adjusting the pH to alkaline and incubating at room temperature to obtain ZnO nanoparticles.

[0006] As a further improvement of the above scheme, the concentration of the poly-C DNA is preferably 4-7 μM.

[0007] As a further improvement of the above solution, the Zn salt is a water-soluble Zn salt.

[0008] As a further improvement of the above scheme, the water-soluble Zn salt is one of Zn(OAc)2, Zn(NO3)2, and ZnSO4.

[0009] As a further improvement of the above solution, the base length of the poly-C DNA is 5-30 base sequences.

[0010] As a further improvement of the above scheme, the preparation method comprises the following steps: placing Zn salt in a poly-C DNA aqueous solution with a concentration of 5 μM and mixing, heating in a water bath to 70-90° C., adding NaOH solution thereto to adjust the pH to alkaline, ultrasonicating for 20-50 minutes and then incubating at room temperature for 1-3 hours to obtain ZnO nanoparticles.

[0011] As a further improvement of the above scheme, the water-soluble Zn salt is Zn(OAc)2.

[0012] As a further improvement of the above scheme, the base length of the poly-C DNA is 20.

[0013] An application of the ZnO nanoparticles obtained based on the preparation method comprises using the ZnO nanoparticles as raw materials to prepare an external gel for wound surface antibacterial treatment.

[0014] Compared with the prior art, the beneficial effects of the present application are as follows: by overall control of the reaction conditions, such as the base composition of the template DNA, the length of the base sequence, and the concentration of the DNA in the reaction system, ZnO nanoparticles with high uniformity, a particle size of less than 300 nm, and a spindle-shaped structure are obtained. Moreover, experiments on mice have shown that the external preparation made from the ZnO nanoparticles obtained in the present invention as raw materials can be used for wound antibacterial treatment, and has a good application prospect in the field of medical antibacterial dressings. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 TEM and EDS analysis results of ZnO nanoparticles obtained in Example 1;

[0017] Figure 2 The UV-visible absorption spectra of the ZnO nanoparticles and reagents obtained in Example 1;

[0018] Figure 3TEM and DLS analysis results of ZnO nanoparticles synthesized with different concentrations of DNA templates;

[0019] Figure 4 The DLS analysis results of ZnO nanoparticles obtained in Examples 2-8 and Comparative Example 3;

[0020] Figure 5 TEM results of ZnO nanoparticles obtained in Examples 2, 4, 7, and 8;

[0021] Figure 6 The DLS and TEM analysis results of ZnO nanoparticles obtained in Comparative Examples 1, 4, 5, and 6;

[0022] Figure 7 TEM results of ZnO nanoparticles obtained in Comparative Examples 7-9;

[0023] Figure 8 The antibacterial effect of ZnO nanoparticles on Staphylococcus aureus and Escherichia coli under light-protected and light-exposed conditions;

[0024] Fig. 9 The wound photos of mice in each group;

[0025] Fig.10 The results are shown for wound tissue fluid plating at different time points. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0027] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0029] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0031] Example 1

[0032] Using poly-C DNA with a base length of 20 (denoted as C20, the same below) as a template, 500 μL of 10 mM Zn(OAc)2·2H2O solution and 50 μL of 100 μM poly-C DNA with a base length of 20 were added to 250 μL ultrapure water in sequence, vortexed to mix, placed in a 85°C hot water bath, and 200 μL of 100 mM NaOH solution was added thereto. After ultrasonication for 30 min, the mixture was incubated at room temperature for 2 h. The reaction solution was centrifuged at 20,000 rpm for 20 min, the supernatant was discarded, and the mixture was washed twice with ultrapure water to obtain DNA-stabilized ZnO nanoparticles.

[0033] DNA was fluorescently labeled with FAM, and ZnO nanoparticles with fluorescent labels were obtained according to the preparation method of Example 1. The morphology and elemental analysis were performed using a transmission electron microscope (TEM) and an energy dispersive X-ray spectrometer (EDS). The results are as follows: Figure 1 The results show that the elements of ZnO nanoparticles are Zn and O, and contain a small amount of P and N, indicating that DNA is adsorbed on the surface of ZnO nanoparticles, and the EDS scanning results also show that DNA is distributed on the cross section of ZnO.

[0034] UV-Vis absorption spectra of ZnO nanoparticles and reagents Figure 2 As shown, C20 refers to the poly-C DNA template with a base length of 20. UV-Vis results show that ZnO nanoparticles have characteristic absorption peaks of DNA and ZnO crystals at 260nm and 360nm.

[0035] The above results show that DNA is fixed on the ZnO nanoparticles obtained in Example 1.

[0036] Comparative Example 1

[0037] According to the preparation method of Example 1, without adding a DNA template, ZnO nanoparticles were obtained.

[0038] Comparative Example 2

[0039] According to the preparation method of Example 1, the concentration of the DNA template in the reaction system was replaced from 5 μM to 10 μM to obtain ZnO nanoparticles.

[0040] The morphology of the ZnO nanoparticles obtained in Example 1, Comparative Example 1, and Comparative Example 2 was observed using TEM and analyzed using a dynamic light scattering particle size analyzer (DLS). Figure 3 The results show that when no DNA template is added to the system, the size of the ZnO nanoparticles formed is 360nm, the PDI is 0.5, and the morphology is uneven; when the DNA template is added to the system with a final concentration of 5μM, the size of the ZnO nanoparticles formed becomes smaller (about 240nm), the uniformity becomes higher (PDI is 0.07), and a uniform spindle-shaped structure is presented; when the concentration of the DNA template is increased to 10μM, although the ZnO nanoparticles still maintain a spindle-shaped structure, the particle size and PDI value are significantly increased.

[0041] Example 2

[0042] The base length of the poly-C DNA template was replaced with 1, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0043] Example 3

[0044] The base length of the poly-C DNA template was replaced with 2, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0045] Example 4

[0046] The base length of the poly-C DNA template was replaced with 5, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0047] Example 5

[0048] The base length of the poly-C DNA template was replaced with 7, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0049] Example 6

[0050] The base length of the poly-C DNA template was replaced with 10, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0051] Example 7

[0052] The base length of the poly-C DNA template was replaced with 15, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0053] Example 8

[0054] The base length of the poly-C DNA template was replaced with 30, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0055] Comparative Example 3

[0056] The poly-C DNA template was replaced with poly-A DNA, poly-T DNA and poly-G DNA with base lengths of 1, 2, 5, 7, 10, 15 and 30, respectively, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0057] The ZnO nanoparticles obtained in Examples 2-8 and Comparative Example 3 were analyzed using DLS. The results are as follows: Figure 4 The results show that when the length of the DNA template is short, the particle sizes of ZnO nanoparticles synthesized by DNA templates with different base sequences are quite different, but as the DNA length increases, this difference gradually decreases, and when the DNA length increases to 30 bases, the particle sizes of ZnO nanoparticles synthesized by DNA templates with different base sequences are basically less than 300nm.

[0058] The morphology of the ZnO nanoparticles obtained in Examples 2, 4, 7, and 8 was observed using a transmission electron microscope (TEM). Figure 5 When the base sequence length of the DNA template in the system is 1, the morphology of the synthesized ZnO nanoparticles is uneven, and a small amount of spindle-shaped structures can be observed in the field of view, but most of them are aggregates of multiple cones; as the base sequence of the DNA template is extended, the morphology of the ZnO nanoparticles gradually changes from disordered to regular spindle-shaped structures. When the base sequence length of the DNA increases to 5, the vertical and horizontal comparisons of the ZnO nanoparticles are close, and the morphology is between the spherical and spindle-shaped structures; when the base sequence length of the DNA is ≥20, the ZnO nanoparticles present a uniform and stable spindle-shaped structure.

[0059] Comparative Example 4

[0060] The poly-C DNA template was replaced with a poly-A DNA with a base length of 20, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0061] Comparative Example 5

[0062] The poly-C DNA template was replaced with a poly-T DNA with a base length of 20, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0063] Comparative Example 6

[0064] The poly-C DNA template was replaced with a poly-G DNA with a base length of 20, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0065] The ZnO nanoparticles obtained in Comparative Examples 1, 4, 5, and 6 were analyzed and tested using DLS and TEM. The results are as follows: Figure 6As shown. The results show that when no DNA template is added to the system, the synthesized ZnO nanoparticles are disordered, uneven, and fragmented in morphology; when poly-A DNA, poly-T DNA, or poly-G DNA templates are added to the system, the ZnO nanoparticles obtained are difficult to form a regular spindle structure, but approaching the spindle shape, they present a broken flower-like structure, an irregular aggregation state, and a loose cone-like aggregation state. Moreover, after adding poly-A DNA, poly-T DNA, or poly-G DNA templates, although the particle size of the ZnO nanoparticles did not change significantly, its uniformity was significantly improved. The above results show that adding different DNA templates to the synthesis system will have a significant effect on the structure and uniformity of ZnO nanoparticles.

[0066] Comparative Example 7

[0067] The poly-C DNA template was replaced with free cytosine, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0068] Comparative Example 8

[0069] The poly-C DNA template was replaced with an A / T double-stranded DNA with a base length of 20, and ZnO nanoparticles were prepared according to the method shown in Example 1.

[0070] Comparative Example 9

[0071] The poly-C DNA template was replaced with a C / G double-stranded DNA with a base length of 20 as a template, and ZnO nanoparticles were obtained according to the preparation method of Example 1.

[0072] The DLS analysis results of the ZnO nanoparticles obtained in Comparative Examples 7-9 are shown in Table 1, and the TEM results are shown in Figure 7 As shown. The results show that the particle size of the ZnO nanoparticles obtained in Comparative Example 7 is about 277nm, which is close to the particle size of the ZnO nanoparticles obtained in Example 1, but its PDI significantly increases to 0.37, indicating that its particle size uniformity is poor, which will cause the particles to be unstable and aggregate. The particle size and stability of the ZnO nanoparticles obtained in Comparative Examples 8 and 9 did not change significantly compared with Example 1, but the microscopic morphology changed significantly. The ZnO nanoparticles obtained in Comparative Example 8 showed a rough conical aggregate structure, while the ZnO nanoparticles obtained in Comparative Example 9 had incomplete C / G20 growth and showed a loose triangular aggregate state.

[0073] Table 1

[0074] template Particle size (nm) PDI Cytosine 277±2 0.37±0.08 A / T20 219±1 0.22±0.05 C / G20 205±4 0.18±0.02

[0075] The above results confirm that the phosphate backbone, base sequence and length of the DNA template have an impact on the morphology, particle size and uniformity of ZnO nanoparticles. Among them, the ZnO nanoparticles synthesized using poly-C DNA with a base length of ≥20 as a template have the most regular spindle-shaped structure, with both a smaller particle size and higher uniformity.

[0076] Test Example 1

[0077] The antibacterial activity of the ZnO nanoparticles obtained in Example 1 against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) before and after illumination was detected by gradient dilution method: ZnO nanoparticles were mixed with bacteria respectively, and cultured continuously in an incubator at 37°C and 180 rpm for 12 h, and then the OD of each group was detected. 600 The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ZnO nanoparticles against different bacteria were detected by the combined plate method. The MIC and MBC results of ZnO nanoparticles against bacteria under different light conditions are shown in Table 2. The antibacterial effects of ZnO nanoparticles at different concentrations are shown in Table 2. Figure 8 shown.

[0078] The results showed that the inhibitory effect of ZnO nanoparticles on the growth of Staphylococcus aureus and Escherichia coli gradually increased with the increase of nanoparticle concentration, and its inhibitory activity was not affected by light, indicating that within this concentration range, there was no obvious correlation between the antibacterial activity of ZnO nanoparticles and their photocatalytic activity, and it was speculated that it was mainly related to the contact between ZnO nanoparticles and bacteria. Through quantitative analysis, the minimum inhibitory concentration (MIC) / minimum bactericidal concentration (MBC) of ZnO for Staphylococcus aureus and Escherichia coli were 80μg / mL and 320μg / mL respectively.

[0079] Table 2

[0080]

[0081] Test Example 2

[0082] Animals and feeding: SPF-grade healthy ICR male mice (6-8 weeks, 20-24 g) were purchased and fostered by the Experimental Animal Center of Central South University. During the feeding period, the animals had free access to food and water, and were placed in a 12-hour light and 12-hour dark cycle every day. All animal experiments were approved by the Experimental Animal Ethics Committee of Central South University (ethics approval number: XMXH--2023-1229).

[0083] Construction of the wound model of Staphylococcus aureus infection in mice: After the mice were anesthetized, a circular full-cut wound with a diameter of 1 cm was constructed on their backs, and then 100 μL of Staphylococcus aureus suspension (1×10 6CFU / mL), and the infection lasted for 24 hours. After bacterial infection, the wound showed obvious suppuration and the healing speed slowed down significantly, indicating the successful construction of the infected wound.

[0084] Gel preparation: The ZnO nanoparticles prepared in Example 1 were prepared into a colloidal solution with a concentration of 40 μg / mL (in terms of Zn), and the solution was mixed evenly with 3% Carbomer 941 gel at a volume ratio of 1:1 to obtain a Carbomer gel containing 20 μg / mL ZnO nanoparticles. A blank gel was prepared by mixing 3% Carbomer 941 gel and double distilled water at a volume ratio of 1:1 as a control.

[0085] Experimental arrangement: The mice were randomly divided into the following 4 groups (n=6): Normal group, Infected group, Blank gel group and ZnO gel group. The mice in Normal group were uninfected normal wound group and did not receive any treatment. The other three groups were infected wound groups. The Infected group did not receive any treatment. The Blank gel group was treated with blank carbomer gel, and the ZnO gel group was treated with ZnO nano-carbomer gel. The drugs were administered (100 μL gel / time) on the 1st day (D1), 3rd day (D3), 5th day (D5) and 7th day (D7), respectively.

[0086] On days 1, 3, 5, 7, 9, and 13, photographs were taken to record the wound conditions of the mice. Fig. 9 The results showed that the wound healing of mice treated with ZnO nanocarbomer gel was better than that of the infected wound group and the blank gel treatment group.

[0087] On the 3rd, 7th and 13th days, mucus from the mouse wounds was smeared on plates and cultured at 37°C for 24 hours before taking photos. Fig.10 The results showed that the use of ZnO-loaded nanogels to treat infected wounds could inhibit the growth of wound bacteria.

[0088] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing ZnO nanoparticles, characterized in that: The following steps are involved: The Zn salt is placed in a poly-C DNA aqueous solution with a concentration of 2-8 μM and mixed evenly, and the pH is adjusted to alkaline and then incubated at room temperature to obtain ZnO nanoparticles.

2. The method for preparing ZnO nanoparticles according to claim 1, characterized in that: The Zn salt is a water-soluble Zn salt.

3. The method for preparing ZnO nanoparticles according to claim 2, characterized in that: The water-soluble Zn salt is one of Zn(OAc)2, Zn(NO3)2, and ZnSO4.

4. The method for preparing ZnO nanoparticles according to claim 1, characterized in that: The poly-C DNA has a base length of 5-30 base sequences.

5. The method for preparing ZnO nanoparticles according to any one of claims 1 to 4, characterized in that: The following steps are involved: The Zn salt is placed in a poly-C DNA aqueous solution with a concentration of 5 μM and mixed, and the mixture is heated in a water bath to 70-90° C., and a NaOH solution is added thereto to adjust the pH to alkaline. After ultrasonication for 20-50 minutes, the mixture is incubated at room temperature for 1-3 hours to obtain ZnO nanoparticles.

6. The method for preparing ZnO nanoparticles according to claim 5, characterized in that: The water-soluble Zn salt is Zn(OAc)2.

7. The method for preparing ZnO nanoparticles according to claim 5, characterized in that: The poly-C DNA has a base length of 20.